Traffic differentiation support in vehicular delay-tolerant networks - Soares, V. N.G.J. (2011)
Submitted by Vasco Soares (vasco.g.soares@ipcb.pt) on 2011-01-27T11:14:51Z No. of bitstreams: 1 TS_rep-ipcb.pdf: 1163405 bytes, checksum: 6044d015ce0ff7c9789c970b9204b9dc (MD5)